Regulatory T Cells and Cardiovascular Diseases - Jevallee, MD, Harish; Tang, MD, PhD, Ting-Ting; Cheng, MD, PhD, Xiang (North American Journal of Medicine and Science, 2011)
Recent researches have substantiated the active participation of chronic low-grade inflammation in cardiovascular disease where immune responses contribute to disease initiation and progression. Regulatory T cells (Tregs) are a unique lineage of T cells and have been proved to play a key role in controlling both the innate and adaptive immune responses under physiological and pathological conditions. Through suppression of immune system activation, Tregs are involved in tolerance to self antigens, thus maintaining immune homeostasis. Existence and function of Tregs were a matter of considerable debate over the last few decades, but owing to innovative molecular categorization of this specialized subpopulation of T cells, they have now been established as fundamental elements in the vertebrate immune system. In view of the prospective therapeutic avenues that Tregs may offer, we hereby review the current knowledge on the role of Tregs immunity in cardiovascular disease.